An adaptive data rate algorithm for improving energy efficiency for multi-gateway LoRaWANs. (8th April 2020) - Chang, Lin-Heng; Chang, Yi; Guan, Chih-Kae; Juang, Tong-Ying; Fang, Wen-Chang
The need of the low power, long range, and low cost connectivity for satisfying the requirement of internet of things (IoT) applications for smart city is leading the emergence of low power wide area (LPWA) networking technologies. The resource efficiency plays an important role in realistic application, LoRaWAN allows the static end devices to individually adapt and optimise the data rates and the transmission power, which is referred to as adaptive data rate (ADR) problem. In this paper, we develop a new ADR algorithm for multi-gateway LoRaWAN environment to quickly choose the appropriate LoRa transmission parameter for independent LoRa end device based on LoRaWAN specification. To successfully execute the ADR algorithm, we especially rewrite the firmware of Semtech's SX1276 transceivers to implement our proposed ADR algorithm over multi-gateway LoRaWAN system, including end device, multi-gateways and network server. Our ADR algorithm utilises the radio link quality, including RSSI, SNR, and packet reception ratio (PRR), from multi-gateways, and the network server determines the appropriate LoRa transmission parameter. Finally, the experimental results illustrate that the proposed algorithm improves the energy efficiency, the effective bit rate, and the battery life of the end device.